Fatores-chave para a inovação no setor público: análise do Prêmio Inova Minas Gerais - Caroline Almeida Nobre (2022)
This dissertation seeks to identify the main drivers and barriers to the implementation of innovation in initiatives awarded by the Inova Minas Gerais Award between the period from 2016 to 2020. Award-winning initiatives were mapped, and barriers and inducers and their potential impacts on the development and implementation of projects were identified. The bibliography provided support for the understanding and definition of key factors, being defined as: internal environment, leadership, resources and external environment. This work used the qualitative research methodology where interviews were carried out with members of the awarded initiatives. As an investigation strategy, the case study was applied, having as research object the Inova Minas Gerais Award in its first five editions. The results found correspond to the key factors defined in the literature and some of these have consequences either as inducers or as barriers to innovation, in this case being called ambivalent. The ambivalent key factors facing the interviewees correspond to the internal environment, leadership and resources. External environment was a key factor cited by respondents only as an inducer and not as a barrier to innovation. Aspects such as recognition arising from the award and personal motivations for participation were perceived as contributing to the participation of public servants in the Inova Minas Gerais Award. reflections for future research were presented in this research, in addition to the opportunities listed regarding the management of the Inova Minas Gerais Award in its next editions, as possibilities for monitoring and perpetuating the awarded initiatives.